An upflow fixed-bed anaerobic–aerobic reactor for removal of organic matter and nitrogen from L-lysine plant wastewater. Issue 3 (1st November 2013) - Messias de Araújo, Moacir; Zaiat, Marcelo
Abstract : This paper reports on the design of a new reactor configuration—an upflow fixed-bed combined anaerobic – aerobic reactor — can operate as a single treatment unit for the removal of nitrogen (≈150 mg N/L) and organic matter (≈1300 mg COD/L) from Lysine plant wastewater. L-Lysine, an essential amino acid for animal nutrition, is produced by fermentation from natural raw materials of agricultural origin, thus generating wastewater with high contents of organic matter and nitrogen. The best operational condition of the reactor was obtained with a hydraulic retention time of 35 h (21 h in the anaerobic zone and 14 h in the aerobic zone) and a recycling ratio ( R ) of 3·5. In this condition, the COD, total Kjeldahl nitrogen (TKN), and total nitrogen (TN) removal efficiencies were 97%, 96%, and 77%, respectively, with average effluent concentrations of 10 ± 36 mg COD/L, 2 ± 1 mg NH4 + -N/L, 8 ± 3 mg Org-N/L, 1 ± 1 mg NH2 − -N/L, and 26 ± 23 mg NH3 − -N/L.